Implementation of Modified Total Physical Response (TPR) Learning Model to Improve Students Learning Achievement in English Speaking - Oktaviani, Kusrini; Siminto, Siminto; Widiastuty, Hesty (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
A Teacher and students are the main aspects of English learning. Collaboration in learning must also fill one another. Students not know much about English, even though there were learning targets that had to be achieved. Meanwhile, English is a lesson that should get a lot of practice. The research gap in this study is the focus on the pronunciation aspect because previous studies only focused on speaking in general. The purpose of this study is to find out Total Physical Response (TPR) leaning model can improve students learning achievement in English speaking. Additionally, this study employs the primary technique of total physical reaction (tpr), which is adjusted by fusing it with a communicative learning strategy to increase the study's accuracy, particularly in terms of improving the students who serve as the research subjects. The findings in this study showed that students were very enthusiastic when practicing, only a littles less confident. However, it will be overcome with a sense of habit from each student. The result is that students have felt a lot of difference in mentioning a vocabulary and no longer hesitate in trying to speak English. Based on the hypothesis results, the students' pretest and posttest scores using the T-test, the hypothesis results indicated that there was no significant difference between the posttest results and the standardized English scores after treatment with the modified Total Physical Response (TPR) learning model. The hypothesis result using the T-Test test is 0.073 which is greater than 0.05 in accordance with the decision-making reference.